Peningkatan Hasil Belajar Siswa Konsep Aritmatika Sosial Dengan Praktek Jual Beli Melalui Pendekatan Saintific di Kelas VII SMP Negeri 1 Sekongkang - Endah Ekowati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
The observations during carrying out the Daily Repetition activities at SMP Negeri 1 Sekongkang showed that learning Social Arithmetic material at the school was not optimal. The purpose of this study is to find out the increase in learning outcomes with the practice of buying and selling through a scientific approach in which there are 4C skills which include Communication, Collaboration, Critical thinking, Creative and innovation in class VII SMP Negeri 1 Sekongkang; Classroom Action Research as a subject for grade VII students and teacher classmates as observers. This class action research uses two cycles. The results of the study there is an increase in student learning outcomes with the practice of buying and selling through the scientific approach which contains 4C in Class VII students of SMP Negeri 1 Sekongkang. This can be seen an increase in the average value in the acquisition of student learning outcomes from the written test which was originally averaged in the Pre Cycle 68.55 to 72.05 in Cycle I and in cycle II experienced a significant increase of 10.22 from the average cycle I result because in the second cycle the average value becomes 82.27.